Life after breast cancer in mutual aid medical associations and hospital patients. - Viola Alles, Alberto; Musé, Ignacio; Vasallo, Alberto; Pees, Graciela; Pacheco, Héctor; Sabini, Graciela; D'Auria, Agustín; Armand Ugon, Alfredo; Matteucci, Pablo; Barlocci, Luis (Cirugía del Uruguay, 1987)
The number of cases surviving breas! cancer is analysed in a group of 459 patients, in clinical stage 1-11-111. Among same, 272 received oncologic assistance al mutual aid associations and 187 at hospital. The age average was 54 in the hospital group and 60 for the above mentioned associations, postmenopausal women being predominan! in both groups, 65% and 79% respectively. In all cases, the therapeutic procedures followed es• tablished patterns. The overall curve of life after breas! cancer is statistically significantly inclined in favor of the group under assistance al mutual aid associations. Similar conditions were found in each clinical stage analysed. The menstrual phase the palien! is going through was found of no value for the prevision of the survival rate. Hypothesis are offered to account for the difierences in behavior of both groups.